Risk prevention evaluation in the incorporation of new drugs for healthcare practices: a methodological proposal - Luis Sánchez-Rubio Ferrández; Concepción Esteban Alba; Ismael Escobar Rodríguez; Ana Such Díaz; Nelida Barrueco Fernández; Javier Sáez de la Fuente (Farmacia Hospitalaria)
Objective: Submit a preventive assessment methodology for the risk of medication errors when incorporating new drugs in clinical practice as well as a description of the types of actions arising from such action. Materials and methods: A Standard Operating Procedure was established which defines and plans the process of assessing the risks of new drugs purchased by the Pharmacy Services before being incorporated into the distribution and dispensation channels. The pharmacist responsible for each area fills the Risk Assessment Form, a questionnaire that facilitates the analysis of the product characteristics and provides guidance on safety measures to be taken depending on the results of that assessment. If it is confirmed that the drug requires some additional security measures to be taken, all professionals and technical staff of the Pharmacy Services shall be informed of measures to be taken. Results: Between 2011 and 2013, 64 drugs were assessed. 35 of them (54.6%) required some additional security measure to be applied before being incorporated into clinical practice. Conclusions: The implementation of the method of preventive risk assessment for new drugs purchased by the Pharmacy Services can be a very useful tool when taking the measures deemed necessary to minimize the likelihood of a medication error occurring before they are incorporated into the distribution/dispensing channels put in place by the Pharmacy Services.